ENSO Variability During the Medieval Climate Anomaly as Recorded by Porites Corals From the Northern South China Sea. Issue 4 (8th April 2021) - Jiang, Leilei; Yu, Kefu; Tao, Shichen; Wang, Shaopeng; Han, Tao; Jiang, Wei
Abstract: The El Niño–Southern Oscillation (ENSO) dominates interannual climate variability worldwide and has important environmental and socio‐economic consequences. However, determining the evolution of ENSO variability and its long‐term response to climate forcing remains an ongoing challenge owing to the limited instrumental records. In this study, we quantified ENSO variability via an empirically calibrated threshold and sliding variance windows using monthly sea‐surface temperature (SST) anomalies based on Porites coral Sr/Ca records from the Xisha Islands in the northern South China Sea. Instrumental SST anomalies from the Xisha Islands correctly captured increasing ENSO variability in the twentieth century, with ENSO detection skills similar to those for Niño3.4 regions. Coral Sr/Ca‐SST anomalies can also serve as sensitive and robust proxies for ENSO variability. Sub‐fossil coral Sr/Ca‐SST anomalies indicated intensified ENSO variability at the end of the Medieval Climate Anomaly (MCA) from 1149 to 1205 ± 4.9 (2σ) Common Era (CE). Combining our records with other ENSO‐sensitive proxy reconstructions from the tropical Pacific, we observed fluctuating ENSO variability during the MCA and intensified ENSO variability for the late MCA. Considering the fewer and low intensity fluctuations associated with external climate forcing and the absence of a coherent temporal correspondence of ENSO activity with solar irradiance and volcanic eruption during the MCA, we hypothesized that the internal dynamics of the climate system play a prominent role in modulating ENSO variability and its evolution, which is supported by unforced climate model simulations and coral reconstructions across the tropical Pacific. Key Points: Coral Sr/Ca‐sea‐surface temperature variations from the northern South China Sea are a reliable proxy of El Niño–Southern Oscillation variability Intensified El Niño–Southern Oscillation variability occurred during the late Medieval Climate Anomaly Unforced internal variability within the climate system likely play a prominent role in modulating El Niño–Southern Oscillation variability